Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/1471-2253-15-18
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic administration of ondansetron in prevention of intrathecal morphine-induced pruritus and post-operative nausea and vomiting in patients undergoing caesarean section

Abstract: BackgroundIntrathecal morphine is commonly used for post caesarean analgesia. However, their use is frequently associated with the incidence of troublesome side effects such as nausea, vomiting and pruritus. Various mechanisms have been postulated for the opioid-induced pruritus, with a variety of medications with different mechanisms of actions formulated for the prevention and treatment. But, the results are inconsistent and hence the prevention and treatment of opioid-induced pruritus still remains a challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 30 publications
0
56
2
1
Order By: Relevance
“…Recently two papers has been published which analyzed the use of prophylactic ondansetron in parturients, and showed conflicting results. In one study, pruritus was reduced by 72%, while in another study there was no reduction in pruritus, both compared to placebo [21] [25]. In our study, there were no differences in the incidence of pruritus and use of antipruritic medication (promethazine).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Recently two papers has been published which analyzed the use of prophylactic ondansetron in parturients, and showed conflicting results. In one study, pruritus was reduced by 72%, while in another study there was no reduction in pruritus, both compared to placebo [21] [25]. In our study, there were no differences in the incidence of pruritus and use of antipruritic medication (promethazine).…”
Section: Discussioncontrasting
confidence: 51%
“…Therefore, we use the NRS as a method of evaluation of pain at rest and on movement in this study [13]. mg prophylactic ondansetron had an incidence of 8% of PONV, whereas those receiving placebo the incidence was 56% [21]. While Imeh et al found an incidence of 9.3% and 37% of PONV when they used dexamethasone plus ondansetron prophylactically compared to dexamethasone in patients who received 0.2 mg of ITM [22].…”
Section: Discussionmentioning
confidence: 97%
“…Obstetric patients received ondansetron before neuraxial morphine administration in only one study . Subgroup analysis showed that pretreatment ondansetron after neuraxial morphine administration was not associated with a decreased rate of pruritus among obstetric patients (RR=0.92, 95% CI 0.81‐1.06, P =.24; Heterogeneity I 2 =61%).…”
Section: Resultsmentioning
confidence: 99%
“…Ondansetron also demonstrated effectiveness reducing postoperative nausea and vomiting, two side effects that were seen more frequently in the placebo group (8% and 56%, respectively) [11]. In another study investigating intrathecal morphine-induced itching, Kung et al prophylactically used 8 mg IV ondansetron during umbilical cord clamping or postoperatively in the postanesthesia recovery room as a therapeutic dose in 82 patients who had undergone cesarean section, while the placebo group received only physiologic saline.…”
Section: Discussionmentioning
confidence: 99%